Impact of urbanization on the marine environment and welfare of small municipal fisherfolks. - De Guzman, P.G. and Dumayas, E.E. (Los Banos, Laguna, Philippines PCAMRD, 1998)
Policy Paper Series No.98-04
Keywords: Fishery policy; Fisheries